Analisis Stilistika dalam Novel Orang-Orang Biasa Karya Andrea Hirata - Nazari, Fadiah; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Language as a literary medium demands uniqueness and finesse in its usage, reflected in literary language that has been tailored by authors to achieve beauty. Stylistics becomes crucial in examining the beauty and precision of language use, even in non-literary contexts. This study aims to analyze the syntactic, lexical, and figurative language structures in the novel "Ordinary People" by Andrea Hirata. Descriptive Analysis method with a qualitative approach is used to achieve this goal. The results show the dominant use of coordinative sentences with declarative sentence types, as well as complex words and connotations commonly used in the novel, making it engaging with the use of figurative devices such as metaphors.